Peradaban Islam Masa Khalifah Rasyidin - Nadila Roselani; M. Ridho Lubis; Syaidatul Azhari; Yetti Ruwina (Journal on Education, 2023)
This study aims to determine the Islamic civilization during the time of the Rashidun caliphs, the Rasyidin Khulafaur were the leaders who replaced the Prophet Muhammad in managing human life who were just, wise, clever, always carried out their duties properly and always received guidance from Allah. The task of the Rashidun Khulafaur was to replace the leadership of the Prophet Muhammad in managing the lives of the Muslims. In the leadership of Abu Bakr, he carried out his power as during the time of the Prophet, was central; Legislative, executive and judicial powers are concentrated in the hands of the caliph. Nevertheless, the caliph also carried out the law. Nevertheless, like the Prophet Muhammad, Abu Bakr always invited his great friends to consult. Umar is known as someone who is good at creating regulations, because he does not only improve and even review existing policies. Caliph Umar has also implemented democratic principles in power, namely by guaranteeing equal rights for every citizen. Caliph Umar was known as a simple man, he even allowed land from colonies to be managed by their owners and even forbade the Muslims to own it, while the soldiers received allowances from the Baitul Mal, which was generated from taxes. The method in this study used the method (library research) by collecting a number of literature relating to the problem and research objectives. Data collection with the results of previous research which supports data on research on Islamic civilization during the time of the Rashidun caliphs.